Smart order as a new instrument for production control - Devis Bartsch; Herwig Winkler (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Smart contracts are transaction programs with an 'if-then logic' in relation to the blockchain technology and offer new possibilities for production control. Smart orders are derived from production orders and they are based on smart contracts. Therefore, they are created with the addition of an 'intelligent' component. Basically, smart orders contribute to the ability of self-organised production systems. Blockchain-technology serves as the necessary infrastructure and, due to its properties, offers additional protection, decentralization and data security Methodology: An extensive literature review is conducted to evaluate the current state of research in the area of the Smart order concept. Based on these results, a concept for the creation and use of smart orders is developed. Findings: According to the literature analyses, preliminary conditions and solutions for blockchain based production control use cases are identified. Based on these findings conceptual considerations are presented for a production control system based on the use of smart orders. Originality: The research shows the status quo of blockchain based solutions in the area of production control. Furthermore, first results of a new production control system based on smart orders is presented. The findings demonstrate the ability of creating self-organized production systems by blockchain technology.
urn:nbn:de:gbv:830-882.0200550; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Artificial Intelligence; Blockhain